Spatial Distribution and Abundance of Emerging Microplastics Pollutants in Groundwater of UAE - Tatan, Bushra (2023)
A Master of Science thesis in Civil Engineering by Bushra Tatan entitled, “Spatial Distribution and Abundance of Emerging Microplastics Pollutants in Groundwater of UAE”, submitted in June 2023. Thesis advisor is Dr. Md. Mortula and thesis co-advisor is Dr. Tarig Ali. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).